PENINGKATAN KEMAMPUAN SISWA MENULIS PUISI DI KELAS VIIIB MTS ALKHAIRAAT BULURI MELALUI OBJEK KONTEKSTUAL - Afriansyah Afrianyah (Scolae: Journal of Pedagogy, 2018)
The formulation of the problem in this study is whether the use of contextual objects can improve students' ability to write poetry. This study aims to improve the ability of class VIII B students in MTs Alkhairaat Buluri to write poetry through contextual objects. And this research can be useful for students, for teachers, and for schools. The design of this study was classroom action research (PTK) which was carried out for two cycles, which included planning, implementation, observation, and reflection. The technique of collecting data through performance tests is writing poetry and observing students and teachers. The results of this study proved significant (1) contextual objects proved to be able to effectively improve the ability to write poetry in class VIII B MTs Alkhairaat Buluri. Improved learning outcomes obtained a class average value of 62% with the percentage of classical learning reaching 55% (less) or 11 students who completed from 20 students who participated in the evaluation in the first cycle and (2) learning outcomes obtained a class average value of 84% with the percentage of classical learning reaching 90% in the second cycle with good qualifications or 18 students completed from 20 students who participated in the evaluation, so the hypothesis in this study was accepted.